Conservation of mangroves in Kuala Perlis, Malaysia : a case study of socio-economic attributes of fishermen driving valuation in sustaining livelihoods through forest management - Zaiton, S; Huda-Farhana, MM; Hasan Basri, Bakti (Forest Research Institute Malaysia, 2019)
A mangrove ecosystem provides a wide range of services which benefit people, society and the economy at large. Local communities are highly dependent on mangrove ecosystems especially for food resources, firewood, charcoal, timber, etc. Mangrove forests are important to fishermen for sustaining rich seafood supplies as a source of income, however due to land conversion to aquaculture and coastal development, mangrove deforestation is faced. Thus it is important that the mangroves in Kuala Perlis are conserved and used by the local community for fishing and aquaculture activities. The fishery sector has a significant impact on the socio-economics of the local community. Face-to-face interviews were conducted among these fishermen. A binary logit model, specifically the Contingent Valuation Method (CVM) was used to determine factors that influenced the fishermen’s willingness to pay (WTP) for conservation. The logit model is one of the most preferred methods that is used to model binary dependent variables in the presence of more than one explanatory variable. The results indicated that the WTP of fishermen was significantly influenced by bid level, education level and marital status. It also shows that socio-demographic factors also influenced the respondent’s willingness to pay for the conservation of nature. These WTP factors are crucial in providing information for better policy options to decision-makers in designing sustainable mangrove forest management for the benefit of the future generations in Malaysia.